A Quasiclassical Study of the F(2P) + CHD3 (v1 = 0,1) Reactive System on an Accurate Potential Energy Surface - Palma, Juliana Isabel (2015)
Quasi-classical trajectories (QCT) have been employed to elucidate the effect of exciting the C-H bond in F + CHD3 collisions. The calculations were performed on a new potential energy surface that accurately describes the van der Waals complexes in the entrance channel of the reaction. It was found that exciting the C-H bond significantly enhances the yield of HF + CD3 while it has a minor effect on the production of DF + CHD2. Therefore, the net effect is that the total reactivity increases upon excitation. This result strongly contradicts recent experimental findings. Significant differences in regard to the yield of each product channel were also found between QCT results calculated with the new surface and those obtained with the surface previously developed by Czakó. This shows that relatively small variations in the topography of the entrance channel can result in huge discrepancies in the predicted DF/HF branching ratio. However, in regard to other attributes of the reaction, the agreement between QCT results computed with different surfaces, and between them and experimental results, is good.For the F + CHD3=>HF + CD3 reaction, at a collisional energy of 9.0 kcal/mol, experiments and QCT calculations agree to indicate that the extra energy deposited in the C-H bond is channelled into the HF product.Besides, the angular distribution of CD3 is backward oriented and is not sensitive to the excitation of the C-H bond.